Assessment of Saudi public knowledge and attitudes toward mental health disorders and its demographic correlation - Mahdy, Marwa Mahmoud Hosny (2022)
The aim of this study is to assess the Saudi public knowledge and attitudes toward mental health disorders and its demographic correlation for Saudi adults attending the primary health care outpatient clinics at Hail city, Saudi Arabia. As mental health is an essential component of health and wellbeing, mental stigma and lack of Knowledge represent a critical obstacle for delivering mental health care. Therefore, it is important to explore the public perception and attitudes regarding mental disorders and people affected by mental disorders. The public knowledge and attitude toward mental health disorders could be improved by conducting a variety of events to promote public education and awareness, Anti-stigma intervention programs and educational programs through mass media to help the general population to decrease stigma toward patients with mental illnesses (PWMI). Increase the community awareness, level of mental health knowledge and decrease the stigma will reflect positively on the management of mental disorder patients, increase the number of mental illnesses help seeker patients, and improve the prognosis, response to treatment and the quality of their life.